Grounded theory in management research - Locke, Karen (SAGE series in management research, 2001)
"This book describes the grounded theory approach for organization and management researchers needing to fully understand the possibilities and challenges of this method. It brings together the broadly dispersed discussions of the logic and practices of grounded theory, restoring this style of qualitative research for students and teachers of organization and management."--Jacket